Evidence of Wild Boars as a Reservoir of Zoonotic Hepatitis E Virus Genotype 3: Implications for Public Health in Argentina - Williman, Macarena Marta (2026)
Hepatitis E virus (HEV) is a global public health concern, causing over 20 million infections annually. It is primarily transmitted via the fecal–oral route, with wild boars and domestic swine as major reservoirs involved in zoonotic transmission. Bahía de Samborombón is an important natural reserve in Argentina characterized by a high population of wild boars, located in a livestock-intensive region near major urban centers. As part of a wild boar control program, 11 sampling campaigns were carried out between 2022 and 2023. Fecal, blood, and liver samples were systematically collected from 80 captured animals for the detection and characterization of HEV through antibody and RNA testing. Serological analysis revealed a positivity rate of 42.4%, whereas RT-qPCR detected HEV RNA in 9.1% of fecal samples and 12.5% of liver samples. From the positive samples, seven viral sequences were recovered using RT-nested PCR, including six from ORF1 and one from ORF2. Phylogenetic analysis clustered these sequences within zoonotic HEV genotype 3, showing a close relationship with human sequences from Buenos Aires and neighboring provinces. This study confirms the presence of HEV in wild boars from Argentina, highlighting the circulation of genotype 3, clade abchijklmno and the associated zoonotic risk.